2021
DOI: 10.1108/joic-12-2020-0048
|View full text |Cite
|
Sign up to set email alerts
|

Cryptocurrency bubble risk and the FOMC announcements during COVID-19 black swan event

Abstract: Purpose After the COVID-19 outbreak, the Federal Reserve has undertaken several monetary policies to alleviate the pandemic consequences on the markets. This paper aims to evaluate the effects of the Federal Reserve monetary policy on the cryptocurrency dynamics during the COVID19 pandemic. Design/methodology/approach We examine the response and feedback effects via an event study methodology. For this purpose, abnormal returns (AR) and cumulative abnormal returns (CARs) around the first FOMC (Federal Open M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These findings are consistent with the results of the majority of studies on conventional market bubbles during the COVID-19 pandemic, such as the work of Gharib et al (2021), who found that several conventional market bubbles mark this period. These findings are also consistent with Jarboui and Mnif (2021) study, which detected several short-lived bubbles in cryptocurrency markets during the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with the results of the majority of studies on conventional market bubbles during the COVID-19 pandemic, such as the work of Gharib et al (2021), who found that several conventional market bubbles mark this period. These findings are also consistent with Jarboui and Mnif (2021) study, which detected several short-lived bubbles in cryptocurrency markets during the COVID-19 pandemic.…”
Section: Resultssupporting
confidence: 93%
“…They were primarily concerned with verifying the impact of these incidents on cryptocurrency volatility. They looked at how monetary and macroeconomic policy announcements can affect Bitcoin prices by using an event analysis approach to justify these connections (Jarboui and Mnif, 2021). Previous financial market research has largely focused on market performance (Fama, 1970;Fama and French, 1998) to detect the presence of bubbles (Fry and Cheah, 2016).…”
Section: State Of the Art And Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the wild fluctuations in cryptocurrency prices, especially in Bitcoin, have gained the attention of mainstream financial research. Some have investigated the transitory effects caused by the COVID-19 pandemic to explain this phenomenon (Caferra and Vidal-Tom as, 2021), while others have focused on identifying the date stamping of these markets' bubbles (Jarboui and Mnif, 2021). Explaining the sources of exceptional cryptocurrency price', dynamics is of great importance for policy and trading decisions.…”
Section: Methodsmentioning
confidence: 99%